Application of the combination of Calontropis gigantea L. and Crescentia cujete L. against Schirpophaga innotata and Leptocorisa acuta Thunb. and predator in paddy plants. Issue 2 (July 2021) - Palayukan, P A; Sjam, S; Melina; Sulaeha; Rosmana, A; Dewi, V S; Budirman
Abstract: C. gigantea L. and C. cujete L. are plants that contain secondary metabolites that can act as insecticides. This study aimed to evaluate the implications of C. gigantea and C. cujete to reduce the population and intensity of attack by stem borer ( S. innotata ) and stink bug ( L. acuta ) which are the main pests of paddy plants. This study consisted of 4 treatments consisting of a mixture of C. gigantea and C. cujete extracts, C. gigantea extracts, C. cujete extracts, and control with 5 replications. The extract made by fermentation ant the extract was applied at the age of 1 month after planting with a concentration of 5% for 8 times with a frequency of 1 time a week. Observation parameters were population and attack intensity of S. innotata and L. acuta as well as natural enemy population. The results obtained were that the treatment of all extracts could reduce the population and intensity of attacks compared to the control. Treatment of the mixture of C. gigantea and C. cujete extracts can reduce the population and the intensity of attacks is higher than without the mixture. Predator is not affected by extract applications.